2017
DOI: 10.1002/ccd.27323
|View full text |Cite
|
Sign up to set email alerts
|

Complete filter‐based cerebral embolic protection with transcatheter aortic valve replacement

Abstract: The left vertebral artery is an important entry route for embolic material to the brain during TAVR. Selective filter protection of the left vertebral artery revealed embolic debris in all patients. The clinical value of complete filter-based TCEP during TAVR warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…In a small study on eleven patients the left vertebral filter could be deployed in nine cases and it contained debris in an equal amount of patients as the Sentinel filters. The size of the captured particles was similar between all filters indicating that the left vertebral artery is an important entry route for debris to the brain during TAVR . Besides the partial protection issue, the fact worth mentioning is that there is only one size of filter available.…”
Section: Cerebral Protection Systemsmentioning
confidence: 81%
“…In a small study on eleven patients the left vertebral filter could be deployed in nine cases and it contained debris in an equal amount of patients as the Sentinel filters. The size of the captured particles was similar between all filters indicating that the left vertebral artery is an important entry route for debris to the brain during TAVR . Besides the partial protection issue, the fact worth mentioning is that there is only one size of filter available.…”
Section: Cerebral Protection Systemsmentioning
confidence: 81%
“…A total of 16 studies, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] including 1170 patients (865/305 with/without EPD), fulfilled the inclusion criteria for the qualitative synthesis ( Figure I in the online-only Data Supplement). The mean age was 81.7 years, and 50.2% were female in 14 studies that reported both age and sex.…”
Section: Study Populationmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][26][27][28][29] The presence of baseline atrial fibrillation was reported in 9 studies, [17][18][19]21,22,26,27,29 with a prevalence of 31.6% (285/902 patients). Previous stroke was reported in 14 studies, [14][15][16][17][18][19][20][21][22][23][26][27][28][29] with a prevalence of 10.8% (111/1028 patients). More details can be appreciated in the Results and Tables I and II in the online-only Data Supplement).…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations